Remaja Sehat, Cantik dan Cerdas tanpa Anemia di Desa Glagahwero - Ekowati, Dyah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
One of the nutritional problems that is still unsolved in the community is anemia. Anemia is a condition of lack of hb levels in red blood cells or erythrocytes. Anemia can occur in a person both at the age of children, adolescents, adults and the elderly (Ministry of Health RI, 2022). According to the World Health Organization (WHO), the prevalence of anemia in the world ranges from 40-88% and the incidence of anemia in young women in developing countries is around 53.7% (Kaimudin, et al., 2017). Based on Riskesdas (2018), the incidence of anemia in young women reaches 32%. This community service was carried out by conducting Haemoglobin (Hb) examinations on 57 young women in Glagahwero Kalisat Village, Jember Regency. Based on the results of examination from 57 young women, 14 adolescents were found to have anemia with hb levels ranging from 10.8-11.4 g / dL. Almost all young women, 55 young women (97%) have received blood-boosting tablets at school while 4 girls (3%) have never received them. All of the young women (100%) had taken blood-boosting tablets. Prevention and treatment of the incidence of anemia in young women is expected to break the chain of anemia in the women's life cycle in the future.